Onychomadesis with lichen planus: An under-recognized manifestation - Chander Grover; Suruchi Vohra (Wolters Kluwer Medknow Publications, 2015)
Onychomadesis or proximal separation of the nail pate usually results from severe, generalized dermatoses like bullous diseases, hand foot and mouth disease, varicella or severe cutaneous drug reactions. Although lichen planus (LP) produces varied nail manifestations (longitudinal onychorrhexis, onychoschizia, nail pigmentation, pterygium etc.), to the best of our knowledge, onychomadesis as a manifestation of nail LP is not recorded. This report presents two children with onychomadesis arising with generalized eruptive LP.